MODERN TECHNOLOGIES IN TEACHING VOCABULARY (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2024)
This bachelor thesis concerns the topic of learning new vocabulary of English as a foreign language. The main question of the research is whether learners are interested in using an online vocabulary learning application.